Schoolbag Weight Carriage in Children: The Analysis of Ground Reaction Forces during Walking, Running and Jumping - Barbosa, João Agostinho Sequeira Pires (2022)
Public society and international scientific community have shown concern about the heavy scholar backpacks carried by children. The possible adverse effects on children’s health of carrying those heavy loads have been in the base of that concern. Thus, the purpose of this thesis was to improve the understanding of school backpacks problem and to contribute to a solution. Specifically, it was our aims: (i) review the existing evidence concerning the characterization of backpack carrying, the known impacts and the solutions; (ii) characterize the loads that students in Portugal carry on their backpacks; (iii) understand how those loads influences the GRF acting on subjects and; (iv) propose modifications on backpack design that do not significantly modifies the main design but can attenuate the GRF magnitude increments. The main conclusions were: (i) scientific community still couldn’t clearly and consistently identified the effects of carrying backpack loads on children health. There are several body structures been studied as they could be affected. Also, there are not a consensus around the load limit that children should carry, however, the limit that seems to be more often recommend is the 10% of the body weight; (ii) the population analysed, students in Portugal, often carried more load than the recommended 10% of body weight. 5th grade students carry more absolute load than the 9th grade students; (iii) the load carried influenced the ground reaction forces. That influence was different in function of the mean of locomotion and the age/school grade, and (iv) with the backpack modification, the introduction of elastic material on the backpack straps, were verified changes on the influence of the backpack carrying in GRF, mainly the decrease of force peaks and loading rate. The main findings of this study confirmed the idea that children in Portugal may be carrying heavier loads on their backpacks than they should, especially the younger ones, and that it influences the ground reaction forces acting on them. However, we saw that is possible to introduce discrete modifications on typical backpacks than can attenuate that effect. It is needed to study, in the future, the way that benefits can be maximized and should not be forgiven the organization/pedagogical measures that may reduce the backpack load.